Occurrence of rare earth elements (REEs) and trace elements (TEs) in feathers of adult and young Gentoo penguins from King George Island, Antarctica. (February 2023) - Espejo, Winfred; Chiang, Gustavo; Kitamura, Daiki; Kashiwada, Shosaku; O'Driscoll, Nelson J.; Celis, José E.
Abstract: Penguins are sentinel species for marine pollution, but their role as potential biovectors of REEs or TEs to ecosystems has been poorly studied. The present study analyzed (ICP-MS) feathers of young and adult Gentoo penguins from Fildes Bay, for 63 elements (including 15 REEs). Most of the REEs were present at very low levels, ranging from 0.002 (Lu) to 0.452 (Sm) μg g −1 d.w., several orders of magnitude lower than TEs. The content of TEs varied widely, with Al, Fe, Zn, Sr, Ba, Ti and Mn as the seven having the highest concentrations in the feathers of both age groups. The results show that P. papua deposits REEs and TEs through the feathers on the penguin rockery, whose potential actual impacts and long-term fate in remote regions need deeper research. This work presents essential baseline data that will be useful for further studies on Antarctic penguins. Highlights: Penguin feathers are useful for monitoring REEs and TEs. Burden of REEs and TEs in feathers reveals bioaccumulation and biomagnification. Wide range of REEs and TEs in feathers of young and adult Gentoo penguins. Toxicological studies are needed to better understand the effects in penguins.